2019
DOI: 10.1186/s13756-019-0580-9
|View full text |Cite|
|
Sign up to set email alerts
|

Susceptibility of livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) to chlorhexidine digluconate, octenidine dihydrochloride, polyhexanide, PVP-iodine and triclosan in comparison to hospital-acquired MRSA (HA-MRSA) and community-aquired MRSA (CA-MRSA): a standardized comparison

Abstract: Background Recent publications have raised concerns of reduced susceptibilities of clinical bacterial isolates towards biocides. This study presents a comparative investigation of the susceptibility of livestock-associated Methicillin-resistant Staphylococcus aureus (LA-MRSA), hospital-acquired MRSA (HA-MRSA) and community-aquired MRSA (CA-MRSA) to the commonly used antiseptics chlorhexidine (CHX), octenidine (OCT), polyhexanide (PHMB), PVP-iodine (PVP-I) and triclosan (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Ignak et al 10 reported that 50% of MRSA and 15% of MSSA had reduced susceptibility to chlorhexidine. Moreover, Dittmann et al 11 reported that 65% of MRSA and 5% of MSSA had decreased sensitivity to chlorhexidine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ignak et al 10 reported that 50% of MRSA and 15% of MSSA had reduced susceptibility to chlorhexidine. Moreover, Dittmann et al 11 reported that 65% of MRSA and 5% of MSSA had decreased sensitivity to chlorhexidine.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the terms "reduced susceptibility" or "increased tolerance" are better used for pathogens exhibiting an elevated MIC to chlorhexidine. 10,11 When the MIC for chlorhexidine was less than 4 μg/mL, the isolates were deemed susceptible. 3,8 Because chlorhexidine can be used in high quantities without causing toxicity, an increase in MIC values does not imply "resistance."…”
Section: Broth Microdilution Test For Chlorhexidinementioning
confidence: 99%
See 1 more Smart Citation
“…[3,5] Over the past 30 years, MRSA infection has become the most common healthcare-associated infection and is highly virulent, aggressive, and drug-resistant. [6,7] MRSA can enter the body through wounds or Pengfei Heng and Bo Shi contributed equally to this work. infected invasive medical devices, resulting in secondary symptoms of infection such as pneumonia, surgical site infections, and bacteremia.…”
Section: Introductionmentioning
confidence: 99%
“…The original article [1] contains an error in Fig. 1 whereby sub-figures 1B, 1C & 1D contain the wrong scale on the x-axis.…”
mentioning
confidence: 99%